The nature of Pu-bearing particles from the Maralinga nuclear testing site, Australia - Megan Cook (Nature Portfolio, 2021)
Abstract The high-energy release of plutonium (Pu) and uranium (U) during the Maralinga nuclear trials (1955–1963) in Australia, designed to simulate high temperature, non-critical nuclear accidents, resulted in wide dispersion µm-sized, radioactive, Pu–U-bearing ‘hot’ particles that persist in soils. By combining non-destructive, multi-technique synchrotron-based micro-characterization with the first nano-scale imagining of the composition and textures of six Maralinga particles, we find that all particles display intricate physical and chemical make-ups consistent with formation via condensation and cooling of polymetallic melts (immiscible Fe–Al–Pu–U; and Pb ± Pu–U) within the detonation plumes. Plutonium and U are present predominantly in micro- to nano-particulate forms, and most hot particles contain low valence Pu–U–C compounds; these chemically reactive phases are protected by their inclusion in metallic alloys. Plutonium reworking was observed within an oxidised rim in a Pb-rich particle; however overall Pu remained immobile in the studied particles, while small-scale oxidation and mobility of U is widespread. It is notoriously difficult to predict the long-term environmental behaviour of hot particles. Nano-scale characterization of the hot particles suggests that long-term, slow release of Pu from the hot particles may take place via a range of chemical and physical processes, likely contributing to on-going Pu uptake by wildlife at Maralinga.